The Outlook for Programmers. - Shein, Esther (Communications of the ACM, 2025)
The article focuses on how generative artificial intelligence (AI) and large language models (LLMs) are helping to cool the job market for computer programmers. Topics include the shift in information technology (IT) jobs, how the COVID-19 pandemic changed company outlooks, and the ways in which this is impacting college graduates.